Characteristics of workplace violence, responses and their relationship with the professional identity among nursing students in China: a multicenter cross-sectional study - Lingyan Zhu; Lu Dongyan; Zhenlan Luo; Xu Mengqi; Linfang Sun; Hu Sanlian (BMC Nursing, 2022)
Abstract Background Nursing students are one of the most vulnerable groups suffering from workplace violence. This study aimed to investigate the workplace violence incidence of Chinese nursing students during clinical practice, to describe the characteristics of violence and students’ responses and to analyse the relationship between the experience of workplace violence and professional identity. Methods A cross-sectional study was conducted among 954 nursing students in ten universities in China through convenience sampling. Workplace violence was surveyed through Hospital Workplace Violence Questionnaire for Nursing Students. Students’ professional identity was measured by Professional Identity Questionnaire for Nursing Students. Statistical methods included descriptive statistics, chi-square test, independent-samples t-test, analysis of variance and linear regression analysis. Results It was found that the incidence of workplace violence among nursing students was 42.98%. The violent incidents ranking from high to low were: verbal abuse, threat, physical attack, sexual harassment, and gathering disturbance. The majority of the nursing students chose to avoid the conflict during the incident. 86.34% of the students didn’t report the incidents. More than half of the victims developed post-traumatic stress disorder after the incidents. Regression analysis results showed that workplace violence experience (β = − 0.076, P < 0.05) was a significantly negative predictor of professional identity. Conclusions Chinese nursing students were exposed to physical and psychological violence during clinical practice with insufficient coping solutions and psychological adjustment. The professional identity of the nursing students was significantly associated with the experience of workplace violence.